Comparison of Normal Vaginal Delivery with or without Antenatal Exercise in Primigravida Presenting in A Tertiary Care Hospital - Faisal Ashraf, Rehana Kanwal, Iram Inam, Memuna Kanwal, Mizrah Mahreen, Tanzeela Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the frequency of normal vaginal delivery in primigravida females with or without antenatal exercise Study design: Randomized Controlled Trial Study Duration: 6 months i.e. 4-5-2021 to 4-11-2021 Setting: Department of Obstetrics & Gynecology, Jinnah hospital, Lahore. Material and methods: 100 females fulfilled the criteria were enrolled. Then females were randomly divided in two groups. In group A, females were advised to do exercise daily. In group B, females were not advised to do any exercise. Then females were followed-up till delivery. Mode of delivery was noted. All this information was collected on proforma. Data was analyzed in SPSS. The study groups were compared by applying chi-square test. P-value ≤ 0.05 was considered as significant. Results: In exercise group, the mean age of patients was 26.00±4.76years. In no exercise group, the mean age of patients was 26.32±4.97years. In exercise group, normal vaginal delivery occurred in 42 (84%) patients. In no exercise group, normal vaginal delivery occurred in 29 (58%) patients. The difference was significant (p<0.05). Conclusion: Thus with exercise, then chances of normal vaginal delivery increase significantly in primigravida. Keywords: Normal vaginal delivery, antenatal exercise, primigravida